The taming of the shrew : texts and contexts - Shakespeare, William, 1564-1616.; Dolan, Frances E. (Frances Elizabeth), 1960- (Boston : Bedford Books of St. Martin's Press, 1996)
This teaching edition of Shakespeare's The Taming of the Shrew reprints the Bevington edition of the play, and is accompanied by four sets of primary documents and illustrations the magically arranged to offer a richly textured understanding of early modern culture and Shakespeare's work within that culture. The texts include facsimiles of period documents, excerpts of conduct literature on marriage and on wife and servant beating, sermons, popular ballads, literary works offering alternative endings to Shakespeare's play, and documents on women's legal status. The primary documents contextualize the plays treatment of assertive women, marital conflict, and domestic disorder and violence.
Introduction: Texts and contexts -- Induction -- Shrews and shrew taming -- Authority and violence in a household: Husbands and wives; masters, mistresses, and servants -- "Feme convert": Katharine's silences -- Achieving the marital ideal: Sun and moon -- Endings and alternatives -- Part one: William Shakespeare, the taming of the shrew -- Part two: Early modern debates -- Alternative endings -- Marriage: An ideal and its contradictions -- "Feme covert": Married women's legal status -- Household: Authority and violence -- Household -- Women's work: Gender and the division of labor -- Wife beating -- Servant beating -- Shrews, taming, and untamed shrews: Shrews and shrew taming -- Analogues to shrew taming -- Untamed shrews -- Bibliography -- Index.
Includes bibliographical references (p. 327-334) and index.
Keywords: Man-woman relationships -- Drama; Married people -- Drama; Padua (Italy) -- Drama; Sex role -- Drama; Comedies; English drama; Shakespeare, William, -- 1564-1616.; Couples -- Italie -- Padoue; Mariage -- Histoire -- Sources; The taming of the shrew (Shakespeare)